SPE Eastern Regional Meeting 2019
DOI: 10.2118/196580-ms
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Rock Properties of the Marcellus Formation – An Experimental Study

Abstract: The Marcellus formation has begun to attract more attention from the oil and gas industry. Despite being the largest shale formation and biggest source of natural gas in the United States, it has been the subject of little research. To fill this gap, this study experimentally examined the rock properties of twenty core samples from the formation. Five tests were performed on the core samples: X-ray computerized tomography (CT) scan, porosity, permeability, ultrasonic velocity, and X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Because the pore throats of shale core samples are very tight, implementing the methods of the conventional porosity measurement might lead to erroneous results. Khalil et al [38] experimentally investigated the effect of injection pressure on porosity measurements of shale core samples using helium at injection pressures of 0.69, 1.38, 2.07, and 2.76 MPa. They claimed that 1.38 MPa is the optimal injection pressure to measure the porosity of shale core samples without damaging the samples, and increasing the pressure above that does not promise significant changes in the porosity measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Because the pore throats of shale core samples are very tight, implementing the methods of the conventional porosity measurement might lead to erroneous results. Khalil et al [38] experimentally investigated the effect of injection pressure on porosity measurements of shale core samples using helium at injection pressures of 0.69, 1.38, 2.07, and 2.76 MPa. They claimed that 1.38 MPa is the optimal injection pressure to measure the porosity of shale core samples without damaging the samples, and increasing the pressure above that does not promise significant changes in the porosity measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have investigated the effects of many parameters, such as gas transport and adsorption effect, pyrolysisinduced thermal maturation, water content, the relationship between static and dynamic properties, temperature, anisotropy, and bedding orientation effects using shale samples (Aljamaan et al 2017;Aljamaan et al 2013;Allan et al 2016;Alnoaimi* et al 2014;Guo et al 2013;He et al 2019;Holt et al 2015;Holt et al 2012;Kim et al 2020;Kuila et al 2011;Lai et al 2016;Masri et al 2014;Sone and Zoback 2013a;Sone and Zoback 2013b;Zhai et al 2021). However, few studies have conducted to examine the rock physical and/or dynamic elastic properties of shale formations (Badrouchi et al 2019;Cho et al 2016;He and Ling 2016;Heller et al 2014;Khalil et al 2019;Ramezanian and Emadi 2020;Sun et al 2016). Heller et al (2014) investigated the effects of confining and pore pressures on matrix permeability of gas-shale plugs from Barnett, Eagle Ford, Marcellus, and Montney reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…The multi-pulse method results showed that this method could reduce anisotropy and heterogeneity effects. Khalil et al (2019) measured samples' porosity from Marcellus formation at four injection pressures (0.69, 1.38, 2.07, and 2.76 MPa). The results showed a direct relationship between the injection pressure and the measured porosity.…”
Section: Introductionmentioning
confidence: 99%